2008
DOI: 10.1103/physrevlett.100.024102
|View full text |Cite
|
Sign up to set email alerts
|

Loss Enhanced Phase Locking in Coupled Oscillators

Abstract: Phase locking, which is achieved by transferring some energy from one oscillator to the others, strongly depends on the coupling strength between the oscillators. Typically, the coupling strength must be above a certain threshold in order to achieve phase locking. Here we show how this threshold can be significantly reduced when phase-dependent losses are introduced into the oscillators. Specifically, the coupling strength can be reduced by at least an order of magnitude, thereby substantially decreasing the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…The loss mechanism plays an important role in phase locking of the array, which may make two sorts of arrays perform differently. 35 Phase locking is a key issue to understand the array of mutually-injected fiber lasers, and many studies were focused on it. Phase locking of the array consisting of a small quantity of fiber lasers was experimentally investigated in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The loss mechanism plays an important role in phase locking of the array, which may make two sorts of arrays perform differently. 35 Phase locking is a key issue to understand the array of mutually-injected fiber lasers, and many studies were focused on it. Phase locking of the array consisting of a small quantity of fiber lasers was experimentally investigated in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…We identified a specific substructure that imposes its synchronization state on the entire network and show that for any coupling configuration the network forms at most two synchronized clusters. Our results indicate that the synchronization state of the network is a nonlocal phenomenon and cannot be deduced by decomposing the network into smaller substructures, each with its individual synchronization state.It is well known that lasers can synchronize to lock their optical phases when the coupling delay time between them is relatively short (compared to the coherence time) [1][2][3][4]. Moreover, optical phase synchronization between two lasers can also occur even when the coupling delay time greatly exceeds the coherence time of the lasers themselves [5][6][7].…”
mentioning
confidence: 98%
“…c 2018 Optical Society of America Phase locking of two coupled lasers operating with only one longitudinal mode was investigated over the years [1][2][3][4]. It was shown theoretically and experimentally that a simple relation exist between the coupling strength that is needed for phase locking and the frequency detuning between the lasers [4][5][6]. While a sharp transition from no phase locking to full phase locking when the coupling strength exceeds a critical value is predicted, the experimental results revealed a gradual transition, which could be explained by introducing noise to each laser [4,6].…”
mentioning
confidence: 99%
“…It was shown theoretically and experimentally that a simple relation exist between the coupling strength that is needed for phase locking and the frequency detuning between the lasers [4][5][6]. While a sharp transition from no phase locking to full phase locking when the coupling strength exceeds a critical value is predicted, the experimental results revealed a gradual transition, which could be explained by introducing noise to each laser [4,6]. For lasers with many longitudinal modes it was shown that for strong coupling strength only common longitudinal modes survive, leading to full phase locking [7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation